Encapsulation of Lactobacillus acidophilus in solid lipid microparticles via cryomilling. Issue 17 (30th November 2022) - Kazemi, Mehran; Shahidi, Fakhri; Javad Varidi, Mohammad; Roshanak, Sahar
Graphical abstract: Highlights: Cryomill was used for the encapsulation of L. acidophilus into SLMs. Encapsulation via cryomilling improved viability of probiotics in harsh conditions. The powder yielded by cryomilling was appropriate to be incorporated into foods. Merits of this method: short processing time, lack of solvents, and low temperature. Abstract: We herein delved into the microencapsulation of Lactobacillus acidophilus (LA) into solid lipid microparticles (SLMs) via the cryomilling technique. For this aim, a frozen lipid mixture containing LA was pulverized at different times (7, 14, 21, 28, and 35 min) using a cryogenic mixer mill to produce probiotic-loaded SLMs. The impacts of different cryomilling durations on the SLMs properties (morphology, particle size, water activity, polymorphism, crystallinity, and thermal behavior) and the viability of LA were evaluated. Microencapsulation improved the viability of LA in simulated gastrointestinal fluids, heat stress, and different concentrations of salt and sucrose. SLMs also were suitable to be incorporated into foods. However, once the cryomilling time was prolonged, the viability of encapsulated LA declined, and particle size grew. The cryomilling technique showed great potential as an alternative approach for encapsulation due to the lack of solvent, short processing time, and simplicity.